Fuel for the work required: a practical approach to amalgamating train‐low paradigms for endurance athletes. Issue 10 (24th May 2016) - Impey, Samuel G.; Hammond, Kelly M.; Shepherd, Sam O.; Sharples, Adam P.; Stewart, Claire; Limb, Marie; Smith, Kenneth; Philp, Andrew; Jeromson, Stewart; Hamilton, D. Lee; Close, Graeme L.; Morton, James P.
Abstract: Using an amalgamation of previously studied "train‐low" paradigms, we tested the effects of reduced carbohydrate (CHO) but high leucine availability on cell‐signaling responses associated with exercise‐induced regulation of mitochondrial biogenesis and muscle protein synthesis (MPS). In a repeated‐measures crossover design, 11 males completed an exhaustive cycling protocol with high CHO availability before, during, and after exercise (HIGH) or alternatively, low CHO but high protein (leucine enriched) availability (LOW + LEU). Muscle glycogen was different ( P  < 0.05) pre‐exercise (HIGH: 583 ± 158, LOW + LEU: 271 ± 85 mmol kg −1 dw) but decreased ( P  < 0.05) to comparable levels at exhaustion (≈100 mmol kg −1 dw). Despite differences ( P  < 0.05) in exercise capacity (HIGH: 158 ± 29, LOW + LEU: 100 ± 17 min), exercise induced ( P  < 0.05) comparable AMPK α 2 (3–4‐fold) activity, PGC‐1 α (13‐fold), p53 (2‐fold), Tfam (1.5‐fold), SIRT1 (1.5‐fold), Atrogin 1 (2‐fold), and MuRF1 (5‐fold) gene expression at 3 h post‐exercise. Exhaustive exercise suppressed p70S6K activity to comparable levels immediately post‐exercise (≈20 fmol min −1  mg −1 ). Despite elevated leucine availability post‐exercise, p70S6K activity remained suppressed ( P  < 0.05) 3 h post‐exercise in LOW + LEU (28 ± 14 fmol min −1  mg −1 ), whereas muscle glycogen resynthesis (40 mmol kg −1 dw h −1 ) was associated with elevated ( P  < 0.05) p70S6K activity in HIGH (53 ± 30 fmol min −1  mg −1 ). We conclude: (1) CHO restriction before and during exercise induces "work‐efficient" mitochondrial‐related cell signaling but; (2) post‐exercise CHO and energy restriction maintains p70S6K activity at basal levels despite feeding leucine‐enriched protein. Our data support the practical concept of "fuelling for the work required" as a potential strategy for which to amalgamate train‐low paradigms into periodized training programs. Abstract : CHO restriction before and during exhaustive exercise impairs exercise capacity but induces work‐efficient cell signalling related to mitochondrial biogenesis. However, restricting CHO and energy intake for 3 h post‐exercise attenuates activation of key signalling proteins regulating muscle protein synthesis (MPS), despite feeding leucine‐enriched protein. Athletes may benefit from reduced CHO availability before and during exercise to enhance mitochondrial related cell signalling but should consume both CHO and protein post‐exercise to restore activation of MPS‐related signalling.